Avantgarde Suomessa - Hautamaki, Irmeli; Piippo, Laura; Sederholm, Helena (Tietolipas, 2021)
Avant-garde in Finland is the first book to provide an overarching introduction to avant-garde art by Finnish artists. The articles in the book discuss the application and development of the cultural ideas of the avant-garde in Finnish art from the early 20th century till the present day. The book focusses on the social, political, and artistic characteristics of avant-garde art and their manifestation in Finnish avant-garde literature, visual arts, architecture, fashion, and music. The book shows the remarkable role of women artists in the development of the Finnish avant-garde. Many artists and groups are presented in the book for the first time. At the same time, the articles highlight connections between well-known Finnish artists and international avant-garde movements that have not been recognized in earlier research. A key theme of the book is the tension between the internationality of avant-garde and the nationalist elements of Finnish culture. The book is peer-reviewed, and its authors are eminent senior scholars and younger researchers.